PERANAN BANTUAN SOSIAL DALAM UPAYA PENGENTASAN KEMISKINAN KELUARGA BURUH TANI - Vina Nurviana; Budiyono Budiyono; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
This research was to investigate the role of social aid to lessen farmer families’ poverty in totokaton, punggur, central Lampung.  It emphasized in income of the families before getting social aid, amount of family’s member, work system, type of social aid utilization, income of the families after getting social aid, hierarchy of minimum staple, and poverty diminution.Descriptive method was used in this research.  The population of this research was 54 farmer families.  The collecting data were observation, questionnaire, and documentation.  Frequency tabulation and percentage were used in this research to analyze the data.  They were the basic of interpretation and description to get the result. The finding of the research showed that   (1) the average of farmer’s income before getting social aid was Rp 7.844.733,33 in each year.  (2)Average of their burden children was 2 people for each patriarch.(3)  it was 81.48% patriarches who used social aid through independent work family system  and  it was 18.52% patriarches through group work system. (4) It was 83.33% patriarches who used social aid in agriculture sector, 16.67% patriarches in non agriculture sector. (5)  Average of income after using social aid was 10.835.006,67% patriarches in every year.  (6)Minimum staple compliance of family was increase from 0% to 48.15% patriarches.  (7)Families who had better life were increase 37.04% which the verge of poverty was 27.78% and better life family was 9.25%.Key words: The social aid, Farmer, Poverty